Increased risk of fatal intoxication and polypharmacy among psychiatric patients at death. Issue 1 (5th October 2020) - Reuss, Christian Fyhn; Hasselstrøm, Jørgen Bo; Linnet, Kristian; Christoffersen, Dorte Jensen; Leth, Peter Mygind; Boel, Lene Warner Thorup; Banner, Jytte
Abstract: Patients suffering from psychiatric disorders have an excess mortality and a shorter life span expectancy compared to the general population. Furthermore, they are treated with multiple drugs and are known to have an increased risk of drug abuse. In this study, we aimed at investigating the pharmaceutical drug and drug of abuse profiles of the deceased included in the Danish prospective autopsy‐based forensic study on psychiatric patients, SURVIVE. Using the postmortem systematic toxicological analysis results, we identified 129 different consumed compounds in our population ( n  = 443). Polypharmacy (≥5 compounds) was detected in 39.5% of the deceased. Deceased with a psychiatric diagnosis or who died from a fatal intoxication had significantly more compounds at the time of their death compared to having either no psychiatric diagnosis or another cause of death, respectively. Evidence of drug abuse was present, as 29.8% of our total population had consumed either methadone or illicit drugs of abuse, excluding tetrahydrocannabinol. Of those deceased with a psychiatric diagnosis, 33.6% had either consumed methadone or illicit drugs of abuse, a greater number than those without a psychiatric diagnosis. Fatal intoxication was the most frequent cause of death (40.6%) with methadone as the major intoxicant. Here, we found that those without a psychiatric diagnosis had fewer fatal pharmaceutical drug intoxications compared to the psychiatric diagnosis groups. Our findings add further context to understanding the excess mortality of psychiatric patents, since there is an increased occurrence of fatal intoxication, polypharmacy, and drug abuse in this population.